Protecting National Honor: Advocating for Legislation Against Cyber Hate Targeting Pakistan’s Armed Forces - Ali Muhammad Imran (Scientific Bulletin)
Cyber hate constitutes a great danger for the Armed Forces of Pakistan, being the reason for diminishing the reputation and culture of discipline among the forces while influencing the general opinion of civilians. Through the discussion of cyberattacks on the military, this article focuses on the ludic nature of military cyberattacks and underlines the necessity for legislative intervention. Lack of respective laws is the main factor behind online defamations and misinformation spread by the Armed Forces. Applying analogy to foreign experience, the article advocates for the implementation of integrated regulatory measures targeted at digital violence. Proposed models provide for jurisprudence and policy principles to provide for strong legal mechanisms that would help formulate holistic national approaches to safeguard the Armed Force’s honor, dignity, and reputation. Nevertheless, these solutions are short of the desired outcomes due to the already highlighted challenges, such as enforcement. The solution to facing these challenges should be to adopt legislative reforms as the main route to maintaining the respect of the Pakistan Armed Forces. Effectively, the reforms can lead the country to stand firmly against the threats that are inherent in the future.